Utilization of Quality Organic Fertilizer at P4S Sari Sedana, Badung, Bali - Situmeang, Yohanes Parlindungan; Mahardika, Ida Bagus Komang; Widyawati , Ida Ayu Trisna; Rematwa, Afelinus (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
This Community Partnership Program (CSP) conducted in Desa Selat, Kecamatan Abiansemal, Kabupaten Badung, has achieved significant advancements in organic agricultural development. The program focused on the implementation of both hard and soft technologies. Hard technologies included the development of high-quality organic fertilizers using local waste materials such as livestock manure, biochar, Trichoderma, NPK fertilizers, and dolomite, processed with simple equipment. These innovations addressed local waste management issues and enhanced agricultural productivity. Soft technologies involved comprehensive training on production management, business operations, and marketing strategies, which empowered the P4S Sari Sedana Group with essential skills for sustainable operation. The program demonstrated high relevance to local needs, effectively transforming waste into valuable resources and introducing environmentally friendly production methods. It also fostered active community participation and generated substantial environmental and economic benefits, including increased soil fertility and reduced reliance on chemical fertilizers. The project produced several key outputs: high-quality organic fertilizer, enhanced community skills, scientific publications, intellectual property registration, and online media coverage. Future sustainability will be supported through institutional capacity building, market expansion, product innovation, and ongoing monitoring and evaluation.